Tunable multiwavelength fiber laser based on bidirectional SOA in conjunction with Sagnac loop mirror interferometer - Sulaiman, Abdul Hadi; Md. Yusoff, Nelidya; Abdullah, Fairuz; Mahdi, Mohd Adzir (Elsevier BV, 2020)
A tunable multiwavelength fiber laser (MWFL) based on bidirectional semiconductor optical amplifier (SOA) in conjunction with a Sagnac loop mirror (SLM) interferometer is proposed. The best multiwavelength spectrum from this setup produces 164 lasing lines within 3 dB uniformity. The main study is to investigate the multiwavelength laser performance by varying the polarization state (PS) at two different locations of polarization controller (PC). Manipulation of a quarter-wave plate (QWP) of PC1 causes PS change before entering polarization-maintaining fiber (PMF) thus affecting the multiwavelength flatness and wavelength bandwidth. Meanwhile, manipulation of QWP of PC2 varied the output power of polarization beam splitter (PBS) and tuned the multiwavelength spectrum with almost similar performance. The multiwavelength tunability, extinction ratio (ER) difference and lasing lines difference is five nm, 2.4 dB and 48 when the QWP angle is adjusted from 0° until 70°, respectively. Lower SOA current reduced the multiwavelength flatness and number of lines. The laser output was found stable at a maximum of 0.31 dB power deviation during the 100 min of stability test.